Estructura asintótica de modelos cosmológicos simples - Moreschi, Osvaldo Mario (1989)
The future null infinity for all non-contracting Robertson-Walker spacetimes is studied systematically. A theorem is proved which establishes the expected relation between the nature of g + and the appearance or absence of cosmic event horizons